2015
DOI: 10.17159/2309-8775/2015/v57n3a5
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of travel time between private car and public transport in Cape Town

Abstract: The objective of urban transportation planning is, or should be, to optimise the access to opportunities for all people. One of the factors that defines access is to minimise the travel time between home and both primary and secondary activities. Optimisation refers to the balance between the benefits of reducing travel time with the cost of that reduction. Cost includes operational, infrastructure and environmental costs. However, the reality in many cities is that travel time is often minimised for some user… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 8 publications
2
15
0
Order By: Relevance
“…Across a number of African cities, bus riders report walking approximately 10 minutes to reach a transit stop, though many walk much longer distances out of necessity (Kumar and Barrett 2008). In Cape Town, South Africa, walking distances to transit are longer than in most cities, with an average of 1.4 km for bus trips and 2.1 km for rail (Hitge and Vanderschuren 2015). In contrast, BRT riders in Bangkok walk an average of just 0.4 km to access the bus, often relying on motorcycle taxis for longer access journeys (Chalermpong and Ratanawaraha 2015).…”
Section: Health Physical Activity and Transitmentioning
confidence: 99%
“…Across a number of African cities, bus riders report walking approximately 10 minutes to reach a transit stop, though many walk much longer distances out of necessity (Kumar and Barrett 2008). In Cape Town, South Africa, walking distances to transit are longer than in most cities, with an average of 1.4 km for bus trips and 2.1 km for rail (Hitge and Vanderschuren 2015). In contrast, BRT riders in Bangkok walk an average of just 0.4 km to access the bus, often relying on motorcycle taxis for longer access journeys (Chalermpong and Ratanawaraha 2015).…”
Section: Health Physical Activity and Transitmentioning
confidence: 99%
“…Similar to Jiao's study, the Cape Town study identified the number of rail and bus stops, the frequency of service for each bus and rail stop per day and the number of bus and train routes. However, based on the South African literature [23], the catchment area per stop was extended from 400 m to 1360 m, accounting for service provision and commuter behaviour in Cape Town.…”
Section: Methodsmentioning
confidence: 99%
“…Travel time between home and activities usually becomes the main parameter for choosing the transport model [60]; for that, travel time can be used to make comparisons between different modes of transportation [61]. The relevance of time savings has also been found to be a key factor in transport improvement schemes [62].…”
Section: Competitiveness Of the Railroad Compared To Roadsmentioning
confidence: 99%